Morphological Characterization of Attakkari Rice Through Natural Field Trials - Gajapathy, K.; Kishanthan, A.; Terensan, S.; Ponnegipprenthiraraja, A. (National Science and Technology Commission, 6th floor, Wing D, Sethsiripaya Stage II, Battaramulla., 2026)
Rice is the staple food for most Sri Lankans, forming the basis of at least two of the three main meals [1]. Among the many rice varieties cultivated in Sri Lanka, Attakkari rice holds a special place due to its cultural significance and historical background. Attakkari rice, also known locally as "Jaffna Red Rice," is a traditional rice cultivar believed to have been introduced to the Kilinochchi region around 2009, likely from India. This cultivar was brought to the Northern region, specifically to the "Vanni" area, during the Sri Lankan Civil War by the then-existing "Porunmiyam" Association according to the farming community [2]. Initially, it was well adapted to the local environment, thriving in the Northern region. However, over time, it became highly susceptible to blast disease caused by Magnaporthe oryzae, a major fungal disease that severely affects rice yields [1]. Despite this vulnerability, many farmers in the Northern region of Sri Lanka continue to cultivate Attakkari, primarily for personal consumption. The cultural significance of Attakkari rice is deeply rooted in the traditional agricultural practices of the region. One of its most notable traits is its resilience against flooding, as the grains do not shatter even under prolonged submersion, making it ideal for regions prone to waterlogging. However, due to its susceptibility to blast disease, the Department of Agriculture, Sri Lanka does not recommend this cultivation [3]. Attakkari rice cultivation in the Northern region of Sri Lanka farmers are typically practiced under low-input management systems. Farmers generally apply minimal fertilizers and adopt simplified management practices compared to those used for other rice varieties. Such low-input approaches reduce production costs while promoting environmental sustainability by minimizing chemical use [2]. In addition, the cultivation of Attakkari rice preserves its inherent nutritional qualities, making it both ecologically sustainable and nutritionally valuable for the region. The cultivation cycle of Attakkari rice, similar to other traditional Sri Lankan rice varieties, is closely aligned with the island’s two major monsoon seasons: Maha (October to March) and Yala (May to September), which provide the essential water required for paddy growth [4]. From a nutritional perspective, Attakkari rice is reported to be richer in essential nutrients [2] compared to many newly improved varieties (Farmers information), which has increased its popularity among health-conscious consumers. Despite these advantages, research on Attakkari remains limited. Moreover, since this variety has been cultivated for over 15 years across different regions of the Northern Province, considerable genetic variability is likely to exist among its populations. Given these factors, exploring Attakkari rice potential for breeding programs is of critical importance, particularly for improving resistance to blast disease, a major constraint in its cultivation. With rising consumer preference and market demand for Attakkari rice this research was undertaken to evaluate the morphological variability of Attakkari rice, confirm morphological variants through field trials, and thereby provide a foundation for breeding efforts aimed at enhancing disease resistance and ensuring the long-term sustainability of this cultivar.